To Stay or to leave : From Tourism Industry to Agriculture as a new economic pillar in Bali - Ida Ayu Putu Widya Indah Sari (Bali Tourism Journal, 2021)
The island of Bali initially was a mere stopover for Dutch vessels. In 1920, It began to invite a massive influx of tourists. The development of tourism in Bali experienced ups and downs with various essential events that occurred to the Indonesian state; From World War II, the War of Independence until the Merger of Bali Island into the Republic of Indonesia on August 17, 1950. Foreign tourists returned to visit the island of Bali after 1950. However, the COVID-19 pandemic in March 2020 switched the reality of the tourism industry. Agriculture became the last pillar for Bali province after the collapse of tourism due to the covid 19 pandemics. People who rely on the tourism sector eventually turned to the agricultural sector. During the pandemic, there was an increase in the workforce in the agricultural sector. This fact is also supported by the results and enthusiasm for high agricultural absorption at the household level. However, in line with the government's attention through Bali Governor Regulation Number 99 of 2018, the government, agricultural practitioners, and the private sector still educate farmers to produce agricultural products following market needs. The use of technology must also be applied to facilitate access to the distribution of farmers' products to buyers. So, with the creation of these new ways, the agricultural sector in Bali will be as strong as tourism.